Influence of intraspecific competition on the distribution of a wide‐ranging, non‐territorial carnivore. Issue 4 (7th October 2013) - Pilfold, Nicholas W.; Derocher, Andrew E.; Richardson, Evan
Abstract: Aim: It is generally held that the dominant competitors in a population will occupy high‐quality habitat while forcing subordinates into lower‐quality habitats through interference competition. We examined the distribution of a non‐territorial apex carnivore relative to foraging habitat to assess the effect of two types of interference: competitive asymmetries in predatory ability and conspecific predation risk. Location: Beaufort Sea, Canada. Methods: The quality of foraging habitat was modelled using resource selection functions to relate the locations of seals killed by polar bears ( Ursus maritimus ) to attributes of the sea ice. We used estimated seal biomass as a sample weight to reflect the energetic return of different sizes of kills. To test the effect of sample weighting, locations at which polar bears were captured were used to compare habitat quality modelled with kills weighted equally and kills weighted by their biomass. The distributions of different demographic classes of polar bears were then compared with the general predictions of unequal‐competitor models. Results: Polar bear distribution was correlated with the quality of the foraging habitat as determined by the kill biomass model ( r s  = 0.90, P  = 0.04), but not in the unweighted design ( P  = 0.75). No difference was detected in use of the highest‐quality foraging habitat by subadults and adults. Females with cubs‐of‐the‐year used lower‐quality foraging habitat relative to the rest of the population. Main conclusions: Weighting the habitat model with biologically relevant information improved its fit to species distribution, and suggested that density of use alone was insufficient to define habitat quality. Intraspecific competition had a varying influence on the distribution: unequal competitors coexisted, while the avoidance of conspecific predation risk resulted in semi‐truncation.